Lack of Follow-up of Prostate-Specific Antigen Test Results - McFall, Stephanie L. (Association of Schools of Public Health, 2009)
OBJECTIVE: We obtained population estimates of the prevalence of lack of diagnostic follow-up after an abnormal prostate-specific antigen (PSA) result and assessed the role of sociodemographic, access, and risk perception factors on follow-up of abnormal tests. METHODS: We used data from the 2000 National Health Interview Survey cancer control supplement. For 3,310 men aged 40 or older with a PSA test, 463 men reported an abnormal PSA test. Outcomes were abnormal PSA and lack of diagnostic follow-up in the latter group. Covariates for logistic regression included sociodemographic variables (age, race/ethnicity, and education), access to care (health insurance and usual source), and risk of cancer (family history and perceived risk). Survey analysis procedures accounted for the complex survey design. RESULTS: Abnormal PSA results were associated with age, family history, and perceived risk of cancer. Approximately 15% of men with abnormal PSA tests reported no follow-up. The estimated number was 423,549 (95% confidence interval [CI] 317,755, 529,343). No follow-up was more likely in Hispanic men (odds ratio [OR] = 2.21, 95% CI 1.04, 4.70) and men without insurance (OR=6.56, 95% CI 2.02, 21.29), but less likely in men with a family history of prostate cancer or higher perceived risk of cancer. CONCLUSIONS: Substantial numbers of men had no follow-up of abnormal PSA tests. Primary care physicians should assess continuity of care following abnormal PSA results. Data about prostate cancer screening and follow-up are needed to support clinical and policy decisions.